309 metagenome assembled microbial genomes from deep sediment samples in the Gulfs of Kathiawar Peninsula - Neelam M. Nathani (Nature Portfolio, 2021)
Measurement(s) marine metagenome • sequence_assembly Technology Type(s) DNA sequencing • sequence assembly process • Binning clustering method Factor Type(s) gulf Sample Characteristic - Environment marine biome • deep marine sediment Sample Characteristic - Location Gulf of Kutch • Gulf of Khambhat • Arabian Sea Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14445387